Design and Construction of Website-based Library Information System Using Laravel Framework at SMP Negeri 3 Lubuk Pakam - Muhammad Rizky Ersa; Fachrid Wadly (Yayasan Sinergi Multidimensi Kreatif, 2024)
School libraries have a very vital role in supporting the teaching and learning process, especially in today's digital era, where fast and efficient access to information is increasingly important. However, many schools, including SMP Negeri 3 Lubuk Pakam, still rely on manual library management, which faces various obstacles such as unsystematic data recording and inefficient book borrowing. To overcome this problem, this study designs and builds a website-based library information system using the Laravel framework. This system is designed to improve the operational efficiency of the library by facilitating access to information, facilitating real-time borrowing and returning books, and supporting users in finding the necessary references. By using Laravel, this system is expected to meet the needs of libraries more quickly and safely. It is hoped that with this information system, library management can be carried out more effectively, increase students' interest in reading, and support a better learning process.